Analysis of epigenetic chromatin modification during mitosis in rice - Guo, Rui; Xue, Chao; Liu, Shuai; Zhang, Mingliang; Gong, Zhiyun (The Indian Journal of Genetics and Plant Breeding, 2016)
DNA methylation and histone modification are two important types of epigenetic modification. In this study, we analyzed the dynamic changes and chromosomal localizations of four different epigenetic modifications, DNA 5-MeC, H3K4me3, H3K9me2, and H3S10Ph, during mitosis in rice. The results showed that signals from DNA 5-MeC and H3K4me3 were distributed in the heterochromatin and euchromatin regions respectively, but no obvious signals from H3K9me2 were detected. There were no significant changes noticed in these three modification patterns at different phases during mitosis. However, the H3S10Ph, which was mainly distributed in the centromeric regions, showed dynamic changes during mitosis that occurred mainly at prophase and anaphase but not at interphase and telophase.